The impact of COVID‐19 pandemic on access to treatment for children with cancer in India and treating center practices. Issue 3 (7th October 2021) - Sharma, Jyotsna; Mahajan, Amita; Bakhshi, Sameer; Patil, Veerendra; Verma, Nishant; Radhakrishnan, Venkatraman; Singh, Amitabh; Kayal, Smita; Seth, Rachna; Pushpam, Deepam; Arora, Ramandeep Singh
Abstract : Background: The coronavirus disease 2019 (COVID‐19) pandemic led the Indian government to announce a nationwide lockdown on March 23, 2020. This study aimed to explore the impact of the pandemic on the accessibility of care for children with cancer and to view strategies adopted by hospitals for service delivery. Methods: Weekly average of childhood cancer (≤18 years) patient registrations during pre‐lockdown period (January 1 to March 23, 2020) were compared with post‐lockdown period (March 24 to May 31, 2020). The effect on the scheduled treatment was investigated for post‐lockdown period. A survey of health care providers was conducted to determine centers' adopted strategies. Results: In 30 participating centers, 1146 patients with childhood cancer (797 pre‐lockdown period and 349 post‐lockdown period) were registered. The weekly average registration was 67.3 and 35.5 patients during pre‐lockdown and post‐lockdown respectively (decline of 47.9%). Although most centers experienced this decline, there were 4 that saw an increase in patient registrations. The distribution of patients registered post‐lockdown was found significantly different by age (lesser older age, P = .010) and distance (lesser travel distance, P = .001). 36.1% of patients, who were scheduled for any of the treatment modalities (chemotherapy, surgery, radiotherapy, and hematopoietic stem cell transplantation) during the post‐lockdown period, experienced delays. Centers adopted several strategies including modifications to treatment protocols, increased use of growth factors, and increased support from social organizations. Conclusions: This multicenter study from India suggests that the COVID‐19 pandemic and the lockdown impacted 2 out of 3 children with cancer. The effect of this on survival is yet to be established. Abstract : The coronavirus disease 2019 pandemic and the national lockdown in India since March 2020 led to delays in diagnosis and interruptions in the treatment of childhood cancer. This study reports a decline of 47.3% in the weekly average patient registration between pre‐lockdown and post‐lockdown, and 36.1% of patients experienced delays in 1 or more treatment modalities during the post‐lockdown period.